Analisis Kesulitan Membaca Permulaan Siswa Kelas 1 pada Mata Pelajaran Bahasa Indonesia SDN17 Parittiga - Sumita, Sumita; Murniviyanti, Liza; Pratama, Aldora (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
This thesis aims to determine the difficulty of early reading and the factors that cause difficulty inreading the beginning of grade 1.B students of SD Negeri 17 Parittiga. The method used in thisresearch is descriptive qualitative method. The data collection carried out by the researcher was an initial reading test, teacher interviews and parental questionnaires. Data analysis uses datareduction, data presentation, and drawing conclusions. The results of this study through pre-reading tests, teacher interviews, and parents' questionnaires for grade 1.B SD Negeri 17 Parittiga resulted that from 21 students 9 students had difficulty reading the beginning which included: reading vowels, consonants, difficult to distinguish between different letters. almost the same as in the form of either capital letters or lowercase letters, reading syllables and not being able to read long sentences properly and correctly. Lack of use of media and learning methods in early reading. The difficulties experienced by students in early reading are influenced by internal and external factors,namely students' lack of interest in learning, the use of learning methods and media that are stilllacking, and parents who are busy with their work so they do not pay attention to the development of children's early reading.